2005
DOI: 10.1111/j.1528-1167.2005.463009.x
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Mania in Patients with Epilepsy

Abstract: Depression has a major impact on quality of life in patients with epilepsy and is also the main risk factor for the increased suicide rate in epilepsy. The frequency of depressive disorders depends on the severity of epilepsy and the localization of the epileptogenic focus, with a prevalence of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 33 publications
(32 reference statements)
5
51
0
4
Order By: Relevance
“…It has been consistently noted that depressive disorders in epilepsy are under-recognized and, consequently, undertreated (Lambert and Robertson 1999;Kanner and Palac 2000;Schmitz 2005). Certainly, the frequent presence of depressive symptoms in epilepsy, which may be milder and more intermittent than those in patients with idiopathic major depression, may contribute to this under-recognition (Lambert and Robertson 1999;Kanner and Palac 2000;Schmitz 2005).…”
Section: Fig 3 Correlation Between Baq and Ids-sr Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been consistently noted that depressive disorders in epilepsy are under-recognized and, consequently, undertreated (Lambert and Robertson 1999;Kanner and Palac 2000;Schmitz 2005). Certainly, the frequent presence of depressive symptoms in epilepsy, which may be milder and more intermittent than those in patients with idiopathic major depression, may contribute to this under-recognition (Lambert and Robertson 1999;Kanner and Palac 2000;Schmitz 2005).…”
Section: Fig 3 Correlation Between Baq and Ids-sr Scoresmentioning
confidence: 99%
“…Certainly, the frequent presence of depressive symptoms in epilepsy, which may be milder and more intermittent than those in patients with idiopathic major depression, may contribute to this under-recognition (Lambert and Robertson 1999;Kanner and Palac 2000;Schmitz 2005). However, even moderate or severe depressive states in patients with epilepsy that might lead to suicide attempts have apparently escaped medical attention.…”
Section: Fig 3 Correlation Between Baq and Ids-sr Scoresmentioning
confidence: 99%
“…These factors in this relatively young patient group can themselves contribute to psychiatric disturbances, as well as biological factors. Numerous studies show that the incidence of psychiatric disorders in PwE is significantly higher than in the general population [2][3][4][5][6][7] . Up to 50 or 60% of patients with chronic epilepsy have at least one mood disorder including depression and anxiety 8 .…”
Section: Introductionmentioning
confidence: 99%
“…One study of 174 patients with epilepsy, using standardized assessment methods based on DSM-IV, found current Axis I disorders in 49%, with anxiety (30.4%) and mood (21.8%) disorders being the most common categories; major depressive episode were the most common individual diagnosis (17.2%) (24). Of depressed patients with epilepsy, the majority suffer from unipolar depression (48). Longitudinal studies in epilepsy and depression reported a bidirectional temporal association between the two conditions: epilepsy was frequently followed by depression, and a history of depression was a considerable risk factor for subsequent epilepsy onset (17,22).…”
Section: Introductionmentioning
confidence: 99%